Integrasi Data Geolistrik (VES) dengan Verifikasi Data Litologi Cutting Bor untuk Menganalisis Lapisan Akuifer - Lulu Setiawati; Agung Wijaya; Valennita; Suhendra; Benny Bayu Prabowo; Rudianto Girsang; Didi Ardiansyah (Mataram University, 2026)
The increasing demand for clean water in Selebar Subdistrict, Sumur Dewa Village, Bengkulu City has prompted research to identify and map aquifer zones more accurately. This study aims to analyze the presence and depth of aquifers using the Vertical Electrical Sounding (VES) geophysical method, which is then verified using borehole lithological data. VES data collection was conducted at three sounding points (n=3) using a Schlumberger configuration with an AB/2 electrode spacing of 250 m. The acquired geophysical data were processed using IPI2win software with an error value (RMS error) >5%, resulting in a one-dimensional (1D) subsurface model that was further developed into a two-dimensional (2D) cross-section. The results indicate that the main aquifer zone is located at a depth of 51–75 meters, characterized by low resistivity values (<50 Ωm), indicating a water-saturated layer identified as the groundwater zone. This is consistent with drilling data, which show indications of water loss at the same depth interval, thereby reinforcing the assumption of groundwater presence in that aquifer layer. Based on these results, it can be concluded that the integration of the VES geoelectric method, verified with borehole cross-section data, is effective in characterizing subsurface structures and mapping aquifer zones more accurately.